A child psychotherapist's way of engaging in assessments for the courts. Issue 3 (1st September 2016) - Sternberg, Janine
Abstract : This paper focuses on assessments to guide decisions made by the courts about placements for children rather than any risk they may pose. The child psychotherapist's specific skills and training which equip them to carry out this work in a distinctive way are described. The paper demonstrates how a child psychotherapist thinks about the material such an assessment might provide and describes the translation work required to provide a meaningful report for the court.